선박 조종성능 평가를 위한 옥외 자유항주모형시험의 불확실성 해석 - 박종열(Jongyeol Park); 서정화(Jeonghwa Seo); 이태일(Taeil Lee); 이대한(Daehan Lee); 박격포(Gyukpo Park); 윤현규(Hyeon Kyu Yoon); 이신형(Shin Hyung Rhee) (大韓造船學會 論文集, 2020)
An outdoor free-running model test system was designed for assessing ship maneuverability with test uncertainty. The test model was a surface combatant of tumblehome hull geometry. The straight forward tests were conducted first to obtain the relationship between the propeller revolution rate and advance speed. During the outdoor tests, the propeller revolution rate to achieve a certain Froude number condition was higher than that in the indoor free-running model tests. Turning circle and zigzag tests for evaluating ship maneuverability criteria were carried out at the propeller revolution rate determined by the straight forward test results. The random and systematic standard uncertainties of maneuvering criteria were obtained by repeated tests and comparison with the indoor free-running model test results, respectively. The test uncertainty was largely dominated by the systematic standard uncertainty, while the random standard uncertainty was small with good repeatability.